The Battle of the Bots: Comparing Google Translate and Kamus-Sunda’s Renditions of Lutung Kasarung Story - Budiarti, Dian (Journal of English Education Forum (JEEF), 2025)
A number of studies comparing the performances of two different machine translators have been widely carried out, but the study of it involving Sundanese language is still scant and needs to be developed. This present study serves to compare the Indonesian-to-Sundanese translations for a short story performed by Google Translate (GT) and Kamus-Sunda (KS). Data were obtained from their Sundanese translations of five-paragraph Indonesian folklore entitled Lutung Kasarung. Furthermore, a number of theoretical frameworks regarding machine translations were used to help analyze the data qualitatively. In general, the findings demonstrate that both GT and KS share a number of similarities and differences in the light of five aspects; (1) improper characters’ names, (2) improper target language, (3) the use of speech level, (4) shifts in meaning, and (5) improper sentence structure. Drawing a brief conclusion, this study found that KS makes less errors rather than GT does, so it can be stated that KS performs better than GT in translating the story.